2014
DOI: 10.1007/s10336-014-1109-x
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal in an extensive continuous forest habitat: Marsh Tit Poecile palustris in the Białowieża National Park

Abstract: Dispersal is one of the least understood features in the life-history of organisms. Theoretical work concentrates on explaining dispersal of organisms in patchy and heterogeneous landscapes, but there are few predictions of dispersal patterns in stable, spatially extensive and largely homogenous landscapes, such as large forests. It is expected that we should observe short-distance dispersal in such places, that, to avoid competition with parents and siblings and incestuous mating, offspring should leave natal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
(79 reference statements)
0
10
0
Order By: Relevance
“…Data on the breeding tits were gathered in four sample plots of 33-54 ha within the Białowieża NP, spaced 1-2 km apart, and covering a total area of ca. 185 ha [their distribution is shown in Wesołowski (2015)]. The study was concentrated in three plots (C, M, and W) situated in oak-lime-hornbeam habitat composed mostly of hornbeam Carpinus betulus, lime Tilia cordata, pedunculate oak, spruce, and Norway maple.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Data on the breeding tits were gathered in four sample plots of 33-54 ha within the Białowieża NP, spaced 1-2 km apart, and covering a total area of ca. 185 ha [their distribution is shown in Wesołowski (2015)]. The study was concentrated in three plots (C, M, and W) situated in oak-lime-hornbeam habitat composed mostly of hornbeam Carpinus betulus, lime Tilia cordata, pedunculate oak, spruce, and Norway maple.…”
Section: Study Areamentioning
confidence: 99%
“…Intensive searches for nests were made each spring, aimed at finding all breeding cavities of Marsh Tits in all the plots (details in Wesołowski 2002Wesołowski , 2015. Moreover, within the plots, all cavities known to have been used for breeding by birds in previous years, situated in living trees up to 5 m above the ground, were checked for the presence of active tit nests.…”
Section: Nest Finding and Retrievalmentioning
confidence: 99%
“…There are likely to be significant risks of starvation and/or predation associated with crossing the more open landscape matrix between woodland habitat patches. There is also no guarantee that even favourable routes such as hedgerows will lead to a vacant patch of suitable woodland in which to settle (Broughton et al 2010;Wesołowski 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Czyż et al (2012) showed that the Marsh Tit population in Białowieża produced offspring with an unbiased sex ratio, reflecting the adult population in the breeding period. However, it is unknown whether the male bias in British populations of adult Marsh Tits results from a male-biased sex ratio among offspring or from differential mortality between full-grown birds, perhaps related to costs associated with female-biased dispersal in fragmented habitat (Broughton et al 2010;Wesołowski 2015). Under the environmental stress of a declining population in fragmented habitat (Broughton and Hinsley 2015) British females could be expected to manipulate their offspring towards daughters, which are rarer, more dispersive and less costly to produce, although manipulation towards males may produce offspring that are more competitively advantaged and able to settle successfully.…”
Section: Introductionmentioning
confidence: 99%
“…The dispersal and settling ecology of Marsh Tits probably make localised founder effects quite unlikely in this species; juveniles invariably disperse out of their natal territories, and in small woods that support only a few pairs these young birds generally leave the wood completely, with any settlers tending to be immigrants that were hatched elsewhere (Broughton et al 2010, Wesołowski 2015). In the 13 ha Odd Quarter and 28 ha Upton Woods in Cambridgeshire, for example, which typically contained two and three breeding territories respectively, none of 88 colour-ringed nestlings subsequently bred in their natal wood, with all of the breeding recoveries (eight records) coming from other woods (pers.…”
Section: Ringing and Migration 2018mentioning
confidence: 99%